Implementasi dan Pendampingan Pembuatan Profil Desa Berbasis Mobile - Soetam Rizky Wicaksono; Felik Sad Windu Wisnu Broto; Paulus Lucky Tirma Irawan (Universitas Muhammadiyah Mataram, 2022)
Abstract: Petungsewu Village is administratively located in Dau District, Malang Regency with a population of 3,336 people. In addition to having good natural resource potential, the village also has promising tourism potential. However, the information has not been distributed properly and widely among public. Therefore, they need information system to distribute information about the village potential. The community service team from Ma Chung University carried out activities to design and create a mobile-based information system for villages with profile content and data on the potential of natural resources and tourism. The methods used are: performance data analysis and collection activities for the system and assistance in the form of installation to training after the end of system work. The results obtained from this activity are in accordance with the objectives, namely the existence of a mobile-based information system for villages, but on the other hand the mentoring process is constrained by the PPKM, so that online implementation is still not optimal and must be continued in the next period offline. But overall this activity has been able to achieve the goals expected by the implementing team and partners.Abstrak: Desa Petungsewu secara administratif terletak di wilayah Kecamatan Dau Kabupaten Malang dengan jumlah penduduk 3.336 jiwa. Selain memiliki potensi sumber daya alam yang baik, desa tersebut juga memiliki potensi pariwisata yang menjanjikan. Namun belum terdistribusikan informasinya dengan baik dan luas. Karenanya dibutuhkan sebuah sistem untuk dapat mendistribusikan informasi tentang desa tersebut. Tim abdimas dari Universitas Ma Chung melakukan aktifitas perancangan dan pembuatan sistem informasi berbasis mobile bagi desa dengan konten profil serta data potensi sumber daya alam dan pariwisata. Metode yang digunakan adalah : aktifitas kinerja analisis data dan pengumpulan untuk sistem dan pendampingan dalam bentuk instalasi hingga pelatihan setelah akhir pengerjaan sistem. Hasil yang didapat dari aktifitas ini telah sesuai dengan tujuan, yakni adanya sistem informasi berbasis mobile untuk desa, namun di sisi lain proses pendampingan terkendala adanya PPKM, sehingga pelaksanaan secara daring masih belum optimal dan harus dilanjutkan di periode berikutnya dengan cara luring. Tetapi secara keseluruhan aktifitas ini telah dapat mencapai tujuan yang diharapkan oleh pihak tim pelaksana dan juga mitra.